Mesoporous silica nanoparticles as anticancer drug carriers in pancreatic cancer treatment - Chung, Shei Li (2025)
Pancreatic cancer, often referred to as “the silent killer”, presents with minimal or no symptoms in its early stages, resulting in late detection. When surgical resection is no longer the optimal treatment option, chemotherapy becomes crucial at this stage. However, the low 5-year survival rate highlights the limited effectiveness of current treatments. In recent years, mesoporous silica nanoparticles (MSNP) have gained significant attention in both scholar and pharmaceutical fields due to their unique combination of properties including stable porous structure and high loading capacities. This research aims to investigate the potential of MSNP as a co-delivery carrier for chemotherapeutic drugs and siRNA. In this project, the chemotherapy drug focused on gemcitabine (GEM), a commonly used chemotherapeutic drug in pancreatic cancer treatment and KRAS-siRNA, a mutated oncogene targeted siRNA. MSNP was successfully synthesized in the laboratory using sol-gel synthesis using tetraethyl orthosilicate (TEOS) as silica source with cetyltrimethylammonium bromide (CTAB) as surfactant template, and comprehensive characterizations were performed through TEM, FESEM, EDX and element mapping, XRD, BET and BJH analysis. The results demonstrate that MSNP exhibits desirable properties for drug delivery, including a stable mesoporous structure with pore size of 4.94 nm, a high surface area of about 278.32 m²/g, particle diameter of approximately 85 nm. MSNP was found to have a crystallinity index of ~ 50.24 % through the usage of XRD, which indicates MSNP was semicrystalline or semi-amorphous material. Additionally, the successful loading of GEM onto MSNP validates the tremendous potential of MSNP as an effective anticancer drug carrier in pancreatic cancer treatment. The highest amount of GEM bounded by 1 mg of MSNP was 8.22 μg. Cytotoxicity test determined the optimum PEI variant was MSNP-PEI (1.2B) which showed the least cytotoxicity in the test. MSNP-GEM-PEI was reported to have minimal anti-proliferation as GEM was encapsulated and not released from PEI coating. Hence, MSNP-PEI-GEM was chosen. Cellular uptake did take place and the rate reduced over time. KRAS siRNA was conjugated to both MSNP-GEM and MSNP-PEI-GEM. By conducting cell viability test on both cell lines AsPC-1 and SW1990, MSNP-GEM demonstrated a promising synergistic and high anti-proliferation effect with a reduction of 73.94 % of cell viability. MSNP-PEI-GEM was reported to have a reduction of 62.67 % of cell viability which made it an alternative treatment plan or design for future. qPCR results supported the findings by showing the knockdown of KRAS gene when comparing only GEM loaded sample to co-delivery sample. These findings provide a valuable reference for future research and investigations in this promising field.